Delayed bladder rupture following blunt trauma: A case report and literature review - Vo Anh Vinh Trang; Nguyen Hai Dang Le; Dai Thanh Sang Nguyen; Phuc Hai Duong; Thien Tan Tri Tai Truyen; Vu Phuong Do (Trauma Case Reports)
Delayed bladder rupture, rare condition following trauma, can result from primary laceration or secondary rupture at the lesion site in the bladder wall. Delayed treatment increases mortality. We report the case of a 43-year-old female who presented with an 8-day history of blunt trauma and a 2-day abdominal discomfort. After using point-of-care ultrasound for abdominal paracentesis to confirm the diagnosis, the patient was transferred to the operating room to suture the ruptured bladder. After nine days, she was discharged free of symptoms. This case report and literature review stress the importance of prompt and appropriate intervention for delayed bladder rupture.